Sobre o número de Milnor de germes de funções holomorfas - Sampaio, Breno Rafael Pinheiro (2015)
In early work on the number of Milnor, it is defined as the dimension of the nth homology group of a Milnor fiber. This work will check some other equivalences, with the aim of showing that the number of Milnor can be written as the demension of a vector C-space that comes from the ratio of the germ ring of holomorphic functions and its Jacobian.